Functionalization and polymerization of plant oil triglycerides - Çaylı, Gökhan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
In this study, new polymers and were synthesized from different plant oil triglycerides by using allylic groups of the triglycerides. Moreover, allylic positions and double bonds of soybean oil were used for preparation of different type of reactive monomers and their polymers. Soybean, cod liver, and linseed oils were polymerized by oil soluble phenolformaldehyde resins in one step. Phenols which were used to prepare oil soluble resoles were p. ethyl, p. tertiary butyl, p. tertiary octyl, and p. phenyl phenols. Among the triglycerides the best polymerization results were obtained from linseed oil. A series of rubbery polymers were synthesized with linseed oil with 40 per cent phenol formaldehyde resins. For other less unsaturated oils, similar results could be obtained with at least 60 per cent phenolic resin use. Among the oil soluble resoles, the best mechanical and thermal properties were obtained with p. ethyl phenol resole. The mechanical properties of p. phenyl phenol resole were better than p. tertiary butyl and octyl resoles. In the second part of the study, soybean oil was first converted to allylic brominated soybean oil by NBS (N-bromo succinimide) and then reacted with acrylate and methacrylate salts, -OCN, -SCN anions and triethyl amine to give allylic acrylate and methacrylate esters of soybean oil, polyisocyanate and polyisothiocyanates of soybean oil and quaternary ammonium salts of soybean oil respectively. Soybean oil was also reacted with iodine isocyanate to give iodo isocyanate addition products of soybean oil. This poly isocyanate was then polymerized with different type of alcohols and amines to give corresponding polyurethanes and polyureas. Also, similar reactions were performed on methyl oleate as a model compound. Allylic acrylate and methacrylate esters of methyl oleate were obtained by the reaction between allylic brominated methyl oleate and acrylic and methacrylic acid potassium salts. Moreover allylic amine of methyl oleate was prepared by the reaction between allylic brominated methyl oleate and NH3 and this monomer was polymerized to give AB type unsaturated fatty based polyamides by amide-ester interchange. In the third, part of this study, acrylated epoxidized soybean oil was polymerized with p. tertiary butyl phenol furfural resin via Diels-Alder reaction to give cross linked polymers. When the polymer was heated above 140 oC, retro Diels-Alder reaction took place with a 60 per cent yields. After cooling of the materials, cross linking was established again. After each heating and cooling cycle the hardness of the polymer increased due to the increasing the cross linking density which was caused from imperfect retro Diels-Alder reaction of furan and acrylate moieties. The chemical, physical and thermal behaviors of the product polymers were characterized.
Keywords: Triglycerides.; Vegetable oils.; Soy oil.; Polymerization.